LSKA-ID: A lightweight security and key agreement protocol based on an identity for vehicular communication - Murtadha A. Alazzawi; Mohammed Tali Almalchy; Ahmed Al-Shammari; Ahmed Salih Al-Khaleefa; Hayder M. Albehadili (Universitas Ahmad Dahlan, 2023)
Recently, a huge effort has been pushed to the wireless broadcasting nature in the open area. However, the vehicular ad hoc network (VANET) is disposed to various kinds of attacks. Hence, keeping the security in VANET is the most critical issue because of the VANET network related to human life. Thus, we propose a robust and lightweight security and key agreement-based identity protocol LSKA-ID for vehicular communication. Our protocol utilizes the elliptic curve cryptography, Chinese reminder theorem, and identity (ID)-based cryptosystem to resolve the issues found in the previously proposed schemes, in which our protocol can resolve the key escrow issues accompanied in most ID-based schemes. Also, it does not need batch verification operations, which cause some problems to the verifier in case the batch beacons have one or more illegal beacons. Moreover, the LSKA-ID protocol addresses the dependency on the trusted authority (TA) during the high frequent handover between the groups that may cause a bottleneck problem on the TA. The security analysis proves the correctness of the LSKA-ID protocol by using the random oracle model and has shown to be effective in a performance evaluation.